High Starch in Diet Leads to Disruption of Hepatic Glycogen Metabolism and Liver Fibrosis in Largemouth Bass (Micropterus salmoides), Which is Mediated by the PI3K/Akt Signaling Pathway - Zhong, Liang; Liu, Hongli; Zhang, Haiqi; Zhang, Weidong; Li, Minghao; Huang, Ya; Yao, Jiayun; Huang, Xiaoli; Geng, Yi; Chen, Defang; Ouyang, Ping; Yang, Shiyong; et al. (Frontiers in Physiology, 2022)
Due to its special flavour and cheapness, starch is a source of nutrition for humans and most animals, some of whom even prefer to consume large amounts of starchy foods. However, the use of starch by carnivorous fish is limited and excessive starch intake can lead to liver damage, but the mechanism of damage is not clear. Therefore, in this study, two isonitrogenous and isolipid semi-pure diets were formulated, respectively. The largemouth bass (Micropterus salmoides) cultured in fiberglass tanks were randomly divided into two groups and fed the two diets for 45 d. Blood and liver were collected for enzymology, histopathology, ultramicropathology, flow cytometry and transcriptomics to investigate the damage of high starch on the liver of largemouth bass and its damage mechanism. The results showed that the high starch not affect the growth performance of largemouth bass. However, high starch caused a whitening of the liver and an increase in hepatopancreas index, aspartate aminotransferase, and alanine aminotransferase in the serum. Histopathological observations showed that high starch led to severe vacuolisation, congestion, and moderate to severe necrotizing hepatitis. The high starch intake led to a significant increase in blood glucose and insulin in serum of largemouth bass, promoting the synthesis and accumulation of large amounts of hepatic glycogen in the liver, leading to the loss of hepatocyte organelles and inducing liver fibrosis. Meanwhile, high starch induced the production of oxidative stress and promoted apoptosis and necrosis of hepatocytes. Transcriptome analysis revealed that there were 10927 and 2656 unique genes in the G and Z groups, respectively. KEGG enrichment analysis showed that 19 pathways were significantly enriched, including glucose metabolism and cell survival. Network mapping based on enrichment pathways and differential expressing genes showed the emergence of a regulatory network dominated by PI3K/Akt signaling pathway. This indicated that the PI3K/Akt signalling pathway plays a very important role in this process, regulating the liver injury caused by high starch. Our results provide a reference for the mechanism of liver injury caused by high starch, and the PI3K/Akt signalling pathway could be a potential therapeutic target for liver injury caused by high starch.